Relative Clause Transfer Strategy and The Implication on Contrastive Analysis Hypothesis - Sudarsono Sudarsono (Universitas Pendidikan Mandalika, 2021)
Foreign language learners may transfer their previous language properties into that of the target language either positively or negatively. The present study was designed to investigate the transfer strategy from the Indonesian relative clauses to the English ones. It was a descriptive study. The data were collected from the theses submitted by the Master's Program students of English Language Education to the university. The study found out that most students relativized subjects successfully but frequently failed to relativize the object of which Indonesian could not do it. The students were not found relativizing indirect objects, oblique, and comparison of which Indonesian did not permit. In conclusion, the study supported the strong contrastive analysis hypothesis.